Teaching Singing in the 21st Century
XVIII, 413 p. 124 illus.
Keywords: This volume brings together a group of leading international researchers and practitioners in voice pedagogy alongside emerging academics and practitioners. Encompassing research across voice science and pedagogy, this innovative collection transcends genre boundaries and provides new knowledge about vocal styles and approaches from classical and musical theatre to contemporary commercial music. The work is sure to be valuable in tertiary institutions, schools and community music associations, suitable for use by private studio teachers, and will appeal to choral leaders and music educators interested in vocal pedagogy.